Effect of drying condition of Thai garlic (Allium sativum L.) on physicochemical and sensory properties - N. Utama-ang (2018)
© All Rights Reserved. This research was conducted to indicate the suitable drying condition of dried garlic powder. The chopped and sliced fresh garlic was dried in hot air oven (40°C and 60°C). The drying process times for chopped and sliced garlic at 60°C (270 and 300 min) faster than 40°C (540 and 630 min). Those drying condition provided the moisture content in the range of 5.42-5.69 with low water activity in the range of 0.514-0.542. The drying temperature and processed condition also affected the colour value (L*, a*, b*). The lightness of dried garlic powder was in the range of 75.53-81.56. The a* and b* value also showed the significant difference with the value in the range of 3.20-4.48 and 23.93-31.05, respectively. Those demonstrated values were significant difference when the temperature was increased whereas the processed garlic size was smaller. The main volatile compounds and aroma characteristics of those dried garlic powders can also identify as allyl methyl sulfide (garlic), diallyl disulfide (onion), and diallyl trisulfide (fried garlic). The sensory evaluation from the chopped garlic at 60°C drying temperature provided the highest rating score in the range of 6.1-6.7, followed by the sliced garlic at 40°C drying temperature (5.9 - 6.7), the chopped garlic at 40°C drying temperature (5.3-5.8), and the sliced garlic at 60°C drying temperature (4.7-5.6), respectively. Those factors were found to be affected toward physicochemical, main volatile content, allicin content, and sensory properties of dried garlic powder which can indicate the suitable drying temperature and processed condition to achieve the good quality of dried garlic powder with acceptable sensory properties.